2009
DOI: 10.4103/0971-9784.53447
|View full text |Cite
|
Sign up to set email alerts
|

Decompression of superior vena cava during bidirectional Glenn shunt

Abstract: Patients undergoing bi-directional Glenn shunt for various congenital anomalies of the heart will have their superior vena cava (SVC) clamped during the procedure. The duration of the procedure is variable, ranging from five to 30 minutes. This can affect the cerebral perfusion due to raised venous pressure [Cerebral blood flow = Mean arterial pressure-(Intracranial pressure + Central venous pressure)]. Shunting away the SVC blood is a well known technique to counter this problem, but we describe two cases whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Maintaining the transcranial pressure greater than 30-40 mm Hg was expected to maintain adequate cerebral perfusion. 10 Elhaddad compared the result of the external shunt with the result of the internal shunt (veno-atrial). In group I, using the veno-atrial shunt, the results during clamping show that the mean SO 2 was 71.3 ± 1.5, the mean SVC pressure before opening the shunt was 40.4 ± 3.4, while after opening the shunt 28.5 ± 3.8.…”
Section: Commentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Maintaining the transcranial pressure greater than 30-40 mm Hg was expected to maintain adequate cerebral perfusion. 10 Elhaddad compared the result of the external shunt with the result of the internal shunt (veno-atrial). In group I, using the veno-atrial shunt, the results during clamping show that the mean SO 2 was 71.3 ± 1.5, the mean SVC pressure before opening the shunt was 40.4 ± 3.4, while after opening the shunt 28.5 ± 3.8.…”
Section: Commentsmentioning
confidence: 99%
“…In a second study, Rodriguez and associates also found significant electroencephalogram changes during SVC clamping. [9][10][11][12][13][14][15][16][17] Clamping the SVC without of temporary shunt can lead to decreased cerebral blood flow and put the brain at risk. Therefore, a temporary shunt is not only necessary during the procedure but also a suitable size cannula is needed to avoid higher SVC pressure.…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations